Synthesis of sulfonamides incorporating piperazinyl-ureido moieties and their carbonic anhydrase I, II, IX and XII inhibitory activity. Issue 18 (15th September 2015) - Congiu, Cenzo; Onnis, Valentina; Deplano, Alessandro; Balboni, Gianfranco; Dedeoglu, Nurcan; Supuran, Claudiu T.
Graphical abstract: K I (hCA I) = 7.5–9490 nM; K I (hCA II) = 0.75–721 nM; K I (hCA IX) = 8.7–517 nM; K I (hCA XII) = 17.0–179 nM. Abstract: By using SLC-0111 (4-fluorophenylureido-benzenesulfonamide), a sulfonamide carbonic anhydrase (CA, EC 4.2.1.1) inhibitor in Phase I clinical trials as an antitumor agent as lead molecule, a series of benzenesulfonamide derivatives incorporating ureido moieties was synthesized. The new compounds contain a 4- N -substituted piperazine fragment in which the ureido linker has been included, and were tested as inhibitors of the cytosolic human (h) hCA I and II isoforms, as well as the transmembrane, tumor-associated enzymes hCA IX and XII. Depending on the substitution pattern at the piperazine ring, low nanomolar inhibitors were detected against all four isoforms, making the new class of sulfonamides of interest for various pharmacologic applications.